KONKURENSI TITIK GERGONNE - Desi Trisna; M. Natsir; Hasriati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses the proof of the concurrent from Gergonne point. The Gergonnepoint of a triangle is the point at which the three lines from vertices to the points oftangency between the incircle and the sides of the triangle are concurrent. ConcurrentGergonne point can be proved through several methods and using Ceva theorem. Theconcurrence of Gergonne point is also proved on excircle of triangle.